2016
DOI: 10.1055/s-0042-108199
|View full text |Cite
|
Sign up to set email alerts
|

Torque-angle-velocity Relationships and Muscle Performance of Professional and Youth Soccer Players

Abstract: CLoKCentral Lancashire online Knowledge www.clok.uclan.ac.uk were found in favor of the U17 group for TTAV and LR outcomes at 120 °/s, 15 however, the PRO group maintained higher torques in both movement directions in 16 comparison to the U17 in TAV3D evaluation. These results suggest that muscle 17 performance of the PRO group is more efficient than the U17 group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The D'Agostino-Pearson normality test indicated that in some angles the SPM violates the normality condition, and thus a twosample non-parametric test was used to compare the torque curves between athletes and non-athletes [15]. The results in ▶Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The D'Agostino-Pearson normality test indicated that in some angles the SPM violates the normality condition, and thus a twosample non-parametric test was used to compare the torque curves between athletes and non-athletes [15]. The results in ▶Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only one, slow angular velocity (20 °/s) was analyzed. It has been reported that the angular velocity of the isokinetic test has a major impact on the torque-angle curves [2,15]. No curve fitting technique was tested to characterize the torque-angle curve features [17], which could reveal new unobserved differences between CG and AG.…”
Section: Discussionmentioning
confidence: 99%
“…All reps were used for the analysis and interpolated for all three angular velocities, in accordance with the duration and values of the average curves for each participant. To better describe surface maps, the entire ROM of extension-flexion motion was considered and polynomial regression curve was plotted for acceleration, constant speed (load range), and deceleration stages of the motion [15,21]. 3D surface maps used Z-axis for the torque value, Y-axis for the angle value, and X-axis for the velocity value.…”
Section: Three-dimensional Surface Mapsmentioning
confidence: 99%
“…Isolated analyses of peak torque, mean power, or total work parameters do not provide insights into the torque-angular velocity relationship of muscle strength. Although this relationship represents the dynamic behavior of the muscle, it also allows for a comprehensive analysis of functional capacity by revealing the lengthening-contraction, and lengthening-velocity relationships [21]. The torque and angle relationship is affected by increasing speed in dynamic evaluations [22].…”
Section: Introductionmentioning
confidence: 99%
“…These outcome variables may provide additional information, such as the time for reaction and the ability to maintain the velocity, which could aid in clinical evaluation and implementation of specific rehabilitation protocols in order to optimize treatment. 17,18 Qualitative analysis of isokinetic output is another form of assessment that uses surface maps of the torque-angle-velocity relationship (TAV 3D ). It can provide a more comprehensive understanding of dynamic behavior of a muscle compared to static assessments, due to focusing on length-tension and length-velocity relationships.…”
Section: Introductionmentioning
confidence: 99%